Enhancement of cell adhesion, retention, and survival of HUVEC/cbMSC aggregates that are transplanted in ischemic tissues by concurrent delivery of an antioxidant for therapeutic angiogenesis. (January 2016) - Huang, Chieh-Cheng; Pan, Wen-Yu; Tseng, Michael T.; Lin, Kun-Ju; Yang, Yi-Pei; Tsai, Hung-Wen; Hwang, Shiaw-Min; Chang, Yen; Wei, Hao-Ji; Sung, Hsing-Wen
Abstract: A recurring obstacle in cell-base strategies for treating ischemic diseases is the significant loss of viable cells that is caused by the elevated levels of regional reactive oxygen species (ROS), which ultimately limits therapeutic capacity. In this study, aggregates of human umbilical vein endothelial cells (HUVECs) and cord-blood mesenchymal stem cells (cbMSCs), which are capable of inducing therapeutic angiogenesis, are prepared. We hypothesize that the concurrent delivery of an antioxidant N -acetylcysteine (NAC) may significantly increase cell retention following the transplantation of HUVEC/cbMSC aggregates in a mouse model with hindlimb ischemia. Our in vitro results demonstrate that the antioxidant NAC can restore ROS-impaired cell adhesion and recover the reduced angiogenic potential of HUVEC/cbMSC aggregates under oxidative stress. In the animal study, we found that by scavenging the ROS generated in ischemic tissues, NAC is likely to be able to establish a receptive cell environment in the early stage of cell transplantation, promoting the adhesion, retention, and survival of cells of engrafted aggregates. Therapeutic angiogenesis is therefore enhanced and blood flow recovery and limb salvage are ultimately achieved. The combinatory strategy that uses an antioxidant and HUVEC/cbMSC aggregates may provide a new means of boosting the therapeutic efficacy of cell aggregates for the treatment of ischemic diseases.